Nuevo registro y confirmación de Leiosaurus paronae (Peracca, 1897) (Squamata: Leiosauridae) en la provincia de San Juan, Argentina - Gómez Alés, Carlos Rodrigo (2017)
We report the first record of Leiosaurus paronae in the department Valle Fértil, San Juan province, Argentina. In December 2015 and January 2016 they were collected and identified two individuals, an adult female (SVL 79 mm) and a juvenile (SVL 44 mm). They were then deposited in the herpetological collection of the Universidad Nacional de San Juan. With this new record, we confirm the presence of Leiosaurus paronae for the province of San Juan.